2015
DOI: 10.4103/1119-3077.151070
|View full text |Cite
|
Sign up to set email alerts
|

Financial barriers to utilization of screening and treatment services for breast cancer: An equity analysis in Nigeria

Abstract: Financial barriers limit the ability of women, especially the poorest SES group, to utilize screening and treatment services for early diagnosis and treatment of breast cancer. Interventions that will improve financial risk protection for women with breast cancer or at risk of breast cancer are needed to ensure equitable access to screening and treatment services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 17 publications
4
36
0
Order By: Relevance
“…Rich households often had more educated residents, enabling them to seek for good health and good services. In agreement with previous studies, financial barriers can prevent those in the poorest socioeconomic status group from utilizing the screening and treatment services for the early diagnosis and subsequent treatment of breast cancer [1012]. The study showed that residential area was associated with mammogram examination and Pap smear screening.…”
Section: Discussionsupporting
confidence: 89%
“…Rich households often had more educated residents, enabling them to seek for good health and good services. In agreement with previous studies, financial barriers can prevent those in the poorest socioeconomic status group from utilizing the screening and treatment services for the early diagnosis and subsequent treatment of breast cancer [1012]. The study showed that residential area was associated with mammogram examination and Pap smear screening.…”
Section: Discussionsupporting
confidence: 89%
“…It further found that a total of 97.9% of respondents had no health insurance coverage [30]. Another study also conducted in Nigeria by Okoronkwo et al, (2015) found that cost of medical treatment and not having insurance coverage was a major financial barrier to utilization and treatment services [64]. These two above mentioned studies are in agreement with our findings in LMICs.…”
Section: Risk Of Bias Across Studiessupporting
confidence: 90%
“…Furthermore, significant discrepancies between needed and provided information are likely also barriers to breast cancer screening, particularly in provinces such as the South of Sumatera and Yogyakarta. Further barriers to breast cancer screening included ethnicity and socio-economic background (Jack et al, 2014;Okoronkwo et al, 2015). It is also important that the limitations of this study be highlighted.…”
Section: Discussionmentioning
confidence: 99%